From the Editor: The New Leisure Class. (March 2021) - Kelly, Rob
Abstract : Soon after I started as a faculty member in 1990, there was an opinion article in The Wall Street Journal . It described faculty members (at least in the U.S.) as the "New Leisure Class, " riffing off the book by Thorstein Veblen in which he coined the term conspicuous consumption. This topic has been revisited many times since, with statistics on the number of hours the average faculty member has contact with students in class and office hours used as evidence of a pretty cushy existence.